2019
DOI: 10.1177/0194599819884902
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated with Balloon Sinuplasty: A MAUDE Database Analysis

Abstract: Objective Balloon sinuplasty utilization has increased significantly since its introduction over a decade ago. However, the most common associated complications are still unknown. The objective of this study was to analyze adverse events related to balloon sinuplasty. Study Design Retrospective cross-sectional analysis. Setting Food and Drug Administration’s MAUDE database (Manufacturer and User Facility Device Experience; 2008-2018). Subjects and Methods The MAUDE database was searched for all reports on adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…1 As the number of BSD cases has increased, so have the number of BSD-related complications. 4 Initial studies reported that complication rates with balloon sinuplasty were as low as 0.01%. 10 Although rare, these complications are not insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…1 As the number of BSD cases has increased, so have the number of BSD-related complications. 4 Initial studies reported that complication rates with balloon sinuplasty were as low as 0.01%. 10 Although rare, these complications are not insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…After these cases, we queried the Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database for reports regarding Relieva Stratus™ MicroFlow Frontal Sinus Spacers, the brand of sinus implant removed from both patients. The MAUDE database was developed by the FDA to compile all adverse events reported for a particular product, and both manufactures, and providers are required to submit reports whenever an adverse event occurs [13]. We identified eight adverse events attributed to the Relieva Stratus™ MicroFlow Frontal Sinus Spacers, two of which were cases of a retained spacer in the frontal sinus [14].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a comprehensive evaluation of use error adverse events decomposed by several key event attributes to address the gaps in the availability of industrywide statistics. Past work has used MAUDE data to examine adverse events associated with specific devices (Hill et al, 2017;Hur et al, 2019;Krouwer, 2018;Shlofmitz et al, 2019) and specific malfunctions (Kohani & Pecht, 2018). The work presented in this paper sought to evaluate adverse events across all devices, specifically for use error.…”
Section: Introductionmentioning
confidence: 99%